ENERGY SAVING IN EXTRACTIVE DISTILLATION - E. A. Anokhina (Тонкие химические технологии, 2013)
The basic approaches are considered to the creation of energy efficient flowsheets for extractive distillation (ED). A brief analysis of works dedicated to the choice of effective entrainer, of optimal ED flowsheets parameters and the use of certain special methods to reduce ED power consumption (heat exchange between the condensing and evaporating streams of various distillation columns, combination of the principle of heat pump and heat and cold supply stepped by the height of column). The focus is the development of energy-saving technologies on the base of the optimal structure of the schema partition identification. The classic ED flowsheets and ED flowsheets with partly coupled thermally and material flows (PTCDS). Algorithms are described for synthesis of flowsheets manifold based on the graph theory. ED flowsheets with PTCDS to separate mixtures of a number of industrial products are demonstrated such as C4 fraction of dehydrogenation ED with acetonitrile, aromatic separation from the reforming and vapor cracking factions with N-formylmorpholine, ethanol-water mixture with ethylene glycol. Analysis of the literature and the author's research showed that the energy efficiency of the PTCDS extractive distillation of various mixtures is quite different: energy consumption reducing in PTCDS can be small (~ 1.5%), such as ED mixtures of ethyl acetate-ethanol with dimethylsulfoxide, and may increases up to 20-30%, as at ED of the mixture acetone-chloroform with N,N-dimethylformamide. At the paper you will find original author's hypothesis about the causes of various energy efficiency of the PTCDS for various mixes separation by ED.